INCREASING INTEREST IN LEARNING HISTORY IN PUBLIC HIGH SCHOOL 4 GORONTALO THROUGH THE ROLE OF TEACHERS - Imula, Rahmat; Yunus, Resmiyati; Manay, Helman (Satmata: Journal of Historical Education Studies, 2024)
This research aims to determine the role of teachers in increasing interest in learning history at SMA Negeri 4 Gorontalo Jl. Brigadier General Piola Isa, East Wongkaditi Village, North City District, Gorontalo City. The approach used in this research is a qualitative approach. The data used is secondary obtained from interviews with teachers and students with a total of 6 respondents. Data collection techniques use observation, interviews and documentation techniques. The results of the research show that there is an increase in interest in studying at SMA Negeri 4 Gorontalo in the subject of History.